Tyrosine Kinase-2, Angiopoietin-2, and Thrombomodulin Axes in the Late-Onset Fetal Growth Restriction: A Prospective Cohort Study - Esra Altan Erbilen; Fusun Gulizar Varol (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Investigating the interaction among three interconnected proteins, namely receptor Tyrosine Kinase-2 (Tie-2), the vascular remodeling cytokine Angiopoietin-2 (Ang-2), and the coagulation inhibitor Thrombomodulin (TM), may offer fresh insights into the multifactorial origins of late-onset fetal growth restriction (LFGR).